Answer:
Step-by-step explanation:
alright lets get started.
Total area of pyramid will be equals to the sum of area of base and the area of all six faces.
area of hexagonal will be = ![\frac{3\sqrt{3} }{2} *a^2](https://tex.z-dn.net/?f=%5Cfrac%7B3%5Csqrt%7B3%7D%20%7D%7B2%7D%20%2Aa%5E2)
Plugging the value of a as 4, the area of base will be :
![\frac{3\sqrt{3} }{2}*4^2= 41.57](https://tex.z-dn.net/?f=%5Cfrac%7B3%5Csqrt%7B3%7D%20%7D%7B2%7D%2A4%5E2%3D%2041.57)
Now the area of one face will be= ![\frac{1}{2} *base*height](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%20%2Abase%2Aheight)
so, the area of one face will be = ![\frac{1}{2} * 4*6=12](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%20%2A%204%2A6%3D12)
So, the area of six faces will be = ![6*12=72](https://tex.z-dn.net/?f=6%2A12%3D72)
So, the total area of pyramid will be = ![41.57+72](https://tex.z-dn.net/?f=41.57%2B72)
So, the total area of pyramid will be 113.57
Hence the answer is 113.57. : answer
Hope it will help :)